2021
DOI: 10.1111/cid.12978
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities of titanium versus zirconia abutments on implant‐supported restorations: Biodiversity composition and its impact on clinical parameters over a 3‐year longitudinal prospective study

Abstract: Background Shifts in microbial communities are common over time, but they may disturb the host‐microbiome homeostasis and result in inflammation of the peri‐implant issues if a dysbiotic biofilm is established. Purpose Considering that different oral substrate surfaces may have a relevant impact on the microbial adhesion and colonization, the aim of this study was to investigate the microbial communities of the biofilm formed on single‐implant restorations using titanium or zirconia abutments and how they corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…, it has been demonstrated that the type of abutment substrate (i.e., titanium vs. zirconia) could have a relevant impact on the microbial adhesion and colonization(de Freitas et al, 2021;de Oliveira Silva et al, 2020). It would be interesting to characterize changes overtime in individual microbiological profile associated to two-piece zirconia implants restored with cemented fibreglass abutments and all-ceramic crowns.…”
mentioning
confidence: 99%
“…, it has been demonstrated that the type of abutment substrate (i.e., titanium vs. zirconia) could have a relevant impact on the microbial adhesion and colonization(de Freitas et al, 2021;de Oliveira Silva et al, 2020). It would be interesting to characterize changes overtime in individual microbiological profile associated to two-piece zirconia implants restored with cemented fibreglass abutments and all-ceramic crowns.…”
mentioning
confidence: 99%